2015
DOI: 10.1039/c5ra17934c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polypropylene/hydrogenated styrene-isoprene-styrene block copolymer blends and fabrication of micro-pyramids via micro hot embossing of blend thin-films

Abstract: Polypropylene (PP)/hydrogenated styrene-isoprene-styrene block copolymer (HYBRAR) blends were proposed as a new material for the fabrication of optical thin-films with regular micro-pyramids via the micro hot embossing of blend thin-films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The rPP exhibited a typical diffraction pattern for PP with signals at 14.4°, 17.2°, 18.8°, 21.7°, and 24.0°, which corresponds to planes of (110), (040), (130), (111)+ (131)+(040), and (060)+(150). These peaks are characteristic for PP α ‐form crystals, and there was no trace ofthe β modification found either in the neat polymer or composites . It could be seen that the peaks shifted to lower diffraction angle, meantime the peak intensity decreased when the matrix was reinforced with 20 wt% ONPF, which implied the formation of intercalation morphology .…”
Section: Resultsmentioning
confidence: 94%
“…The rPP exhibited a typical diffraction pattern for PP with signals at 14.4°, 17.2°, 18.8°, 21.7°, and 24.0°, which corresponds to planes of (110), (040), (130), (111)+ (131)+(040), and (060)+(150). These peaks are characteristic for PP α ‐form crystals, and there was no trace ofthe β modification found either in the neat polymer or composites . It could be seen that the peaks shifted to lower diffraction angle, meantime the peak intensity decreased when the matrix was reinforced with 20 wt% ONPF, which implied the formation of intercalation morphology .…”
Section: Resultsmentioning
confidence: 94%
“…The visible light transmittance for RF was over 93% at 400 nm and around 99% at 700 nm, which indicates that 7–1% of the light was absorbed by the film in this spectral range [see Figure (A)]. Literature reports indicated that the materials with similar values of transmittance were cataloged as transparent materials. The low transparency of the NRF is due to proteins, lipids, and other components of the NR.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows the XRD patterns for both pure PP and the samples containing the 5 masterbatches studied. The XRD patterns of all the samples show three strong peaks at 2θ angles of around 14 º (110), 16.8 º (040), 18.4 º (130) and two overlapping peaks at 2θ angles of 21 º (111) and 21.8 º (041) [30][31][32]. The small peak at a 2θ angle of ~ 25.3 º (150, 060) which corresponds to the α-crystallite phase is also observed in all the samples [31].…”
Section: Xrd and Ftir Analysismentioning
confidence: 99%